(3eSFhdjI CYVGA eLdS EOGQI TQcI GdeSGgeI Yf bQGQGJ eLdS GdEOGQI (B: s (3OQGSI ebGQfI aj GdbGfhf GdeUQj h GdchjJj (B/ s - (3agO eMeO MGeO TOGO GdMHjfj GdYGRejs; (3eMehO eNJGQ CMeO HQjQjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3JYJHQ GdLeYjI GdYGeI aj TQcI GdeSGgeI UGMHI GdSjGOI fXQjG(B: (3dcf GdhGbY GdYedj jTgO VYa GdLeYjGJ GdYGeI(B: (3MjK CUHMJ CTHg HHQdeGf ZGFH Ch LgGR UhQj aj GdTQcI eeG LYd eLdS GdEOGQI gh GdeSFhd Yf GdfghV aj GdTQcI(B. (3cjajg JTcjd eLdS GdEOGQI h GNJUGUGJg eLdS GdEOGQI h GdJTcjd GdOGNdi deLdS GdEOGQI h GLJeGYGJg h ecGaBJg(B. (3GdgjFGJ GdQbGHjI Ydi GdTQcGJ GdeSGgeI (B: (3h eSFhdjI CYVGA eLdS GdEOGQI(B: (3h OYGhi GdeSFhdjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2010s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B308-317s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdLeYjI GdYGeI aj TQcI GdeSGgeIs; (3bQGQGJ eLdS GdEOGQI s; (3eSFhdjI CYVGA eLdS TQcI GdeSGgeIs; (3JTcjd eLdS GdGOGQIs; (3OYhi GdeSGge GdaQOjIs; (3bjhO OYhi GdeSFhdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs